2018
DOI: 10.1038/s41438-018-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptomic and metabolomic analyses of a wax deficient citrus mutant exhibiting jasmonic acid-mediated defense against fungal pathogens

Abstract: Naturally, resistant crop germplasms are important resources for managing the issues of agricultural product safety and environment deterioration. We found a spontaneous mutant of ‘Newhall’ navel orange (Citrus sinensis Osbeck) (MT) with broad-spectrum protections against fungal pathogens in the orchard, postharvest-storage, and artificial inoculation conditions. To understand the defense mechanism of MT fruit, we constructed a genome-scale metabolic network that integrated metabolome and transcriptome dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 58 publications
(98 reference statements)
0
31
0
Order By: Relevance
“…Reallocation of carbon flux from cuticular wax into plastid membrane lipids in MT Previously, He et al 4 reported that a decreased wax content at the mature stage results in the glossy surface of the mutant. Our research further demonstrates that wax biosynthesis in MT had already been inhibited at the fruit expansion stage, and the inhibition reached the highest level in the mature stage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reallocation of carbon flux from cuticular wax into plastid membrane lipids in MT Previously, He et al 4 reported that a decreased wax content at the mature stage results in the glossy surface of the mutant. Our research further demonstrates that wax biosynthesis in MT had already been inhibited at the fruit expansion stage, and the inhibition reached the highest level in the mature stage.…”
Section: Discussionmentioning
confidence: 99%
“…The total wax was extracted according to a previously reported method 4,23 . Intact fruits were immersed in chloroform for 2 min, twice.…”
Section: Total Wax Extraction and Analysis By Gc-msmentioning
confidence: 99%
See 3 more Smart Citations